An allelopathic plant facilitates species richness in the Mediterranean garrigue. (1st November 2013) - Ehlers, Bodil K.; Charpentier, Anne; Grøndahl, Eva; Callaway, Ray
Summary Positive plant–plant interactions are known to increase species richness in stressful and poor habitats that are often species poor, but the role of facilitative interactions in species‐rich communities is less well understood. It has been proposed that allelopathic plants may create non‐transitive species interactions, which increase species coexistence, and that such indirect facilitation may be important in species‐rich communities. We examined species richness in 12 different plant communities all dominated by the aromatic Thymus vulgaris that produces monoterpenes known to inhibit germination and growth of other plants. We found consistently, and across communities, higher species richness in microsites with thyme than without. Species richness in microsites with, respectively without, two other perennial plants did not differ, suggesting that increased species richness in thyme microsites is due to the presence of thyme. We found a more similar species composition among thyme microsites and positive estimates of thyme on landscape richness enhancement, indicating that thyme also affect richness at the community level. However, across communities, we did not find species consistently confined to thyme microsites, albeit within communities some plants were exclusive to thyme. Abundance of a dominant grass was reduced in microsites where thyme produces the monoterpene carvacrol, suggesting that one mechanism by which thyme facilitates species richness was by the repression of a superior competitor that could allow other species to persist. However, this does not explain higher species richness in microsites of thyme producing other monoterpenes. We discuss how chemical variation in thyme and adaptation of associated species to local monoterpenes may affect richness and community diversity. Synthesis. Allelopathic plants are generally believed to negatively impact upon the performance of associated species. However, allelopathic plants may be important determinants of species richness at the community level by creating microenvironments where species‐specific interactions differ. Our finding shows that thyme increases species richness both locally and at the community level by creating a mosaic of thyme‐modified and unmodified microsites differing in richness and composition. We suggest that this may also apply to other aromatic plants common in Mediterranean vegetation.